Analisis Penggunaan Spesifikasi Bahan Baku terhadap Laba Perusahaan Studi Kasus pada Pt Rimantara Putra Persada - Darno Darno; Eka Nur Laili; Eko Purwanto; Jaya Adi Gama Tengtarto; Kuswana Rama Destian (Neraca : Jurnal Akuntansi Terapan, 2021)
The research aims to find out the analysis of the use of raw material specifications on company profits. Sources of date used in this study are primary data and secondary data, where primary data is obtained directly from PT. Rimantara Putra Persada while secondary data were obtained from theory. Data analysis techniques use descriptive qualitative research method is research on the problem in the form of fact that currently exist in the company, while qualitative approach is a research procedure that produces descriptive data in the form of written or oral words from people and observed behaviors. The results of this study explained that the specification of standart type 79 thermo plastic paint raw material resulted in a profit percentage of 0,39%, the full type of 79 resulted in a profit percentage of 0,48% and full type of 98 resulted in a profit percentage of 0,13%. So that the most relative products genere profit to the company, namely the specification of raw materials thermo plastic paint type full 79.